Effect of alloy composition on machining parameters and surface quality through comprehensive analysis - Shailesh Rao A.; Srilatha Rao (Frontier Materials & Technologies)
This study examined the influence of alloy composition (mild steel and aluminium) on several machining parameters, such as temperature, cutting force, surface roughness, and chip morphology. Significant variations in these parameters were detected by modifying the alloys while maintaining constant process conditions. In mild steel, rotating speed affected chip morphology, with elevated speeds resulting in continuous chips and reduced rates yielding shorter chips. The augmented rake angle affects the chip properties, resulting in a little decrease in chip length. Moreover, the cutting force influenced the chip length at a designated rotational speed. Conversely, aluminium alloys continuously generated continuous chip fragments irrespective of cutting speed or rake angle. Favourable correlation coefficients are noted among the variables, and a regression model is effectively developed and utilised on the experimental data. The random forest model, indicates that material selection significantly influences temperature, cutting force, surface roughness, and chip morphology during machining. This study offers significant insights into the correlation between tool rake angle and other machining parameters, elucidating the elements that influence surface quality. The results enhance comprehension of machined surface attributes, facilitating the optimisation of machining operations for various materials.